MODEL PEMBELAJARAN KOOPERATIF SEBAGAI SALAH SATU ALTERNATIF DALAM PROSES PENDIDIKAN AGAMA KATOLIK DI SEKOLAH - Gabriel Sunyoto (Lembaga Penelitian STKIP Widya Yuwana, 2018)
One of the important components in education is the learning process in the classroom. In such a process teacher should play the role of a facilitator and motivator, rather than a main actor who develop only a silent and apathetic culture amongst the students. In order to have a true role a teacher must be wise in choosing the learning models. The learning models choosen should be appropriate with the students and materials characteristic, student’s background, developmental psychology and morality (moral development). Considering that the range of the catholic religious education consists of student personality, Jesus Christ, the Church and society, cooperative learning models can be used as an alternative choice in the learning process in the classroom.